Measuring Efficiency and Total Factor Productivity using Data Envelopment Analysis: An Empirical Study from Banks of Turkey - Kılıç Depren, Serpil; Depren, Özer (International Journal of Economics and Financial Issues, 2016)
The main purpose of this study is to assess the performance of deposit banks operating in the Turkish Banking Sector for the years 2014-2015 using Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) methodologies. In the light of this aim, 21 deposit banks’ data obtained from The Banks Association of Turkey between 2014 and 2015 is used. There are 2 inputs and 2 outputs variables for Production Approach and 3 inputs and 3 outputs variables for Intermediation Approaches. To measure productivity changes over time, MPI index is calculated from DEA scores. Thus, the influencing factors of relative efficiency and the efficient (or inefficient) banks are determined. As a result, Average # of Staff per Branch, Total personal expenses/Total assets and Total deposits/Total assets have important role for efficiency in production approach. In intermediation approach, Non-interest expenditure/Total assets, Total loans/Total assets and Non-interest income/Total assets are associated with the efficiency. Keywords: data envelopment analysis; Turkish banking sector; Malmquist productivity index JEL Classifications: C440, G210